Reflections of Faith (‘Aqidah) on Arts: A Comparative Analytical Study on Islamic and Western Arts - Qatawneh, Mohammad Abdelhamid Salem; Rababah, Yaser Ahmed Salem (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The study attempts to explore the philosophical, intellectual view of Islamic art that is based on monotheism (tawhīd), and the reflections of ‘aqīdah on it. The study foundationally examines and compares the structures of art within Western mindsets, which stem from pagan embodiments, such as the Greeks and contemporary Darwinism. The study also comes to respond to those who claim that Islamic art stands at the limits of ornamental decorations, or that Islamic art is nothing but a progression of Hellenistic Roman art. The analytical method was employed to examine intellectual texts and their reflections on art in its applied form. A comparative approach is also used in comparing concepts from the Islamic ‘Aqīdah with other theologies and their reflections on art. This study concluded that Islamic art stems from the spirit of tawhīd, consistent with the harmony and oneness of existence. Additionally, Islam was found to be a liberation for art, as it puts artists in the position of choice rather than restricting them in a specific artistic formula as in other ideologies. On the other hand, the study also reveals that the epistemological theory of Western art emerges from a pagan ground or an atheist thought, since it is unable to comprehend the metaphysical world. As a result, nature has entered the list of ‘sanctities’ in the perception of some of the Greek artists and philosophers, which in turn reflected on the purpose of art and its aesthetic role in existence.